THE PROBLEM OF EQUIVALENCE IN TRANSLATION AND THE TERMIN SYSTEM OF THE TRANSLATION LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article discusses the issue of translation, its equivalence, translation as a means of intercultural communication, and the relativity of the result of the translation process. The concept of “thermosystem of language” is also considered, which is part of the lexical system of the national language, since it, to one degree or another, reflects its national and cultural specificity, as well as the subject-conceptual area of knowledge in a specific disciplinary area.